2010
DOI: 10.1590/s0066-782x2010000100006
|View full text |Cite
|
Sign up to set email alerts
|

A importância de um EGC normal em síndromes coronarianas agudas sem supradesnivelamento do segmento ST

Abstract: Background: Admission ECG has a major impact on the diagnosis and management of non-ST elevation acute coronary syndromes (ACS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…Although hospital mortality in patients with ACS who had a normal ECG on admission is lower than in patients with ECG abnormalities, it has been shown that patients with MI and normal ECG on admission do not always have a favorable hospital course and that hospital mortality is as high as 5.7% ( 10 ). In previous studies, patients with a normal ECG were younger, had a lower Killip class on admission and a higher LVEF, while there were no significant differences in risk factors for cardiovascular disease, family history of CAD and previous treatments ( 11 ). In our study, patients with normal ECG were on average 60 years old, and in >90% of cases had preserved LVEF, while diabetes mellitus was present in a quarter of cases, which corresponds to the prevalence of diabetes in patients with ACS ( 12 ).…”
Section: Discussionmentioning
confidence: 88%
“…Although hospital mortality in patients with ACS who had a normal ECG on admission is lower than in patients with ECG abnormalities, it has been shown that patients with MI and normal ECG on admission do not always have a favorable hospital course and that hospital mortality is as high as 5.7% ( 10 ). In previous studies, patients with a normal ECG were younger, had a lower Killip class on admission and a higher LVEF, while there were no significant differences in risk factors for cardiovascular disease, family history of CAD and previous treatments ( 11 ). In our study, patients with normal ECG were on average 60 years old, and in >90% of cases had preserved LVEF, while diabetes mellitus was present in a quarter of cases, which corresponds to the prevalence of diabetes in patients with ACS ( 12 ).…”
Section: Discussionmentioning
confidence: 88%
“…A study by Teixeira et al, further observed that 22% of patients with a normal ECG went on to develop an NSTEMI, which on a practical level forces the clinician to achieve a precise clinical and biochemical characterisation, considering that a normal ECG may not necessarily be a benign finding. We believe that ischemic changes are dynamic and can thus evade detection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 A eficácia do tratamento do IAM está relacionada ao tempo de instituição da terapia de reperfusão, ou seja, a recanalização arterial em tempo hábil poderá proporcionar inúmeros benefícios para o aumento da sobrevida. [4][5][6] Sobretudo, é a terapia mais importante no tratamento, sendo sua indicação associada à clínica e as alterações eletrocardiográficas. 7,8 A reperfusão pode ser realizada com agentes fibrinolíticos, com intervenções mecânicas (angioplastia primária) ou revascularização cirúrgica.…”
Section: Asunclassified
“…14 Contudo, este exame deve ser realizado em até 10 minutos após a chegada do paciente ao hospital. 6,9,12 No entanto, o retardo desse atendimento torna impossível à terapêutica com trombolíticos. Os estudos mostram que o tratamento com trombolíticos iniciado na primeira hora é muito mais eficaz, com diminuição do risco de mortalidade, do que quando é iniciado após 6 a 12 horas do início do sintoma.…”
Section: Asunclassified